2008
DOI: 10.1038/ki.2008.97
|View full text |Cite
|
Sign up to set email alerts
|

AP214, an analogue of α-melanocyte-stimulating hormone, ameliorates sepsis-induced acute kidney injury and mortality

Abstract: Sepsis remains a serious problem in critically ill patients with the mortality increasing to over half when there is attendant acute kidney injury. alpha-Melanocyte-stimulating hormone is a potent anti-inflammatory cytokine that inhibits many forms of inflammation including that with acute kidney injury. We tested whether a new alpha-melanocyte-stimulating hormone analogue (AP214), which has increased binding affinity to melanocortin receptors, improves sepsis-induced kidney injury and mortality using a cecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 55 publications
2
82
3
2
Order By: Relevance
“…These results name, for the first time, MC peptides with the group of proresolving mediators. We speculate that this effect can be relevant to the tissue-protective properties of AP214 19 and other MC agonists. 50 In all our settings, these proresolving effects require MC 3 expression.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These results name, for the first time, MC peptides with the group of proresolving mediators. We speculate that this effect can be relevant to the tissue-protective properties of AP214 19 and other MC agonists. 50 In all our settings, these proresolving effects require MC 3 expression.…”
Section: Discussionmentioning
confidence: 86%
“…AP214 displays tissue-protective effects against renal postreperfusion injury, 19,20 but the mechanisms behind these tissue-protective actions have not been elucidated. Besides studying the anti-inflammatory and anticytokine effects of AP214 in mice and in cells bearing inactive MC 1 or nullified for MC 3 , we describe the proresolving nature of AP214 on the process of phagocytosis and efferocytosis, a new aspect of MC-based therapy.…”
mentioning
confidence: 99%
“…In a study using the cecal ligation and puncture animal model of sepsis, Doi et al showed marked functional and histologic protection against AKI and reduced mortality when AP214 was administered at 0 and 6 hours before surgery and, most interestingly, even when it was administered up to 6 hours after surgery. 3 In a phase IIa study, AP214 administered in a dose of 600 mg/kg around the time of cardiac surgery decreased the incidence of AKI. 4 In a phase IIb randomized, double-blind, placebo-controlled study for the prevention of AKI in patients undergoing highrisk cardiac surgeries, ABT-719 significantly reduced the composite endpoint consisting of death, need for RRT, or a 25% reduction in renal function during a 90-day postoperative period.…”
Section: A-melanocyte-stimulating Hormonementioning
confidence: 99%
“…1,2 Some critical animal studies demonstrated that a-MSH protects from AKI due to ischemia-reperfusion, 2 nephrotoxins, and sepsis. 1,3 AP214 is an a-MSH analogue with a 10-fold greater affinity for the melanocortin-1 receptor compared with native MSH that has been developed by Action Pharma and licensed recently by Abbott/AbbVie as ABT-719. In a study using the cecal ligation and puncture animal model of sepsis, Doi et al showed marked functional and histologic protection against AKI and reduced mortality when AP214 was administered at 0 and 6 hours before surgery and, most interestingly, even when it was administered up to 6 hours after surgery.…”
Section: A-melanocyte-stimulating Hormonementioning
confidence: 99%
“…We induced sepsis by CLP surgery with 8-mm cecal ligation, which causes modest sublethal sepsis in normal outbred CD-1 mice. 8 All animals survived until they were killed at 18 h after surgery. CLP surgery in non-nephrectomized mice caused a numerically small, but not significant increase of serum creatinine (sham BNx ϩCLP group).…”
mentioning
confidence: 99%